A non-compensatory approach to the creation of composite indices of agricultural sustainability of the European Union countries. (9th November 2022) - Marković, Milan; Stanković, Jelena J.; Marjanović, Ivana; Tsaples, Georgios
The paper aims to calculate and evaluate the degree of achieved agricultural sustainability in the countries of the European Union. Agriculture is a specific activity that, on the one hand, must provide sufficient amounts of food for the population, while on the other hand, it can have a significant negative impact on the environment. The assessment of agricultural sustainability was made by selecting ten relevant indicators from the Eurostat and OECD databases, and by creating a composite index using the Mazziotta-Pareto method. The research results show that the Northern Europe countries (Sweden, Finland and Denmark) achieve the highest level of agricultural sustainability, mainly due to the high participation of organic agricultural production, as well as the low level of soil erosion, considering all European countries. On the contrary, countries with high agricultural economic performance show significantly worse results in terms of sustainability (such as Italy, Spain and France).